Pengaruh Pembelajaran Socio-Scientific Issues dalam Mata Kuliah Konsep Dasar IPA SD terhadap Kemampuan Argumentasi Calon Guru SD - Putri, Agnesi Sekarsari; Rakhmawati, Yeni; Syamsi, Ibnu (Universitas Muhammadiyah Magelang, 2025)
This study aims to improve the argumentation skills of pre-service primary teachers through learning socio-scientific issues in the introductory science concepts course. This study is a quasi-experimental study using a nonequivalent pretest-posttest control-group design. The sample in this study was 126 prospective primary school teachers selected using the cluster random sampling technique. The instruments in this study consisted of four essay-type questions. The test questions were analyzed using One-way ANOVA with SPSS 22 and the gain score test. The results showed differences in argumentation skills between the experimental class, control class 1, and control class 2. The increase in argumentation skills of prospective primary school teachers in the experimental class was higher than in control class 1 and control class 2. Learning socio-scientific issues in the introductory science concepts course can be an alternative for lecturers to develop the argumentation skills of pre-service primary teachers.